Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1108/sjme-09-2018-0043
|View full text |Cite
|
Sign up to set email alerts
|

Engaging customers through user-and company-generated content on CSR

Abstract: Purpose This study aims to analyze the role of corporate social responsibility (CSR) customer perceptions, customer–company identification and customer trust on customer engagement (CE), paying special attention to the moderating effects of two types of social media communication, firm-generated content and user-generated content. Design/methodology/approach The study uses a mixed-methods’ approach. First, a single-factor experiment using Twitter posts as stimuli with 227 hotel guests. The structural model w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 134 publications
3
43
1
Order By: Relevance
“…So, the findings of the present study confirmed that customer CSR engagement on social media positively relates to E-WOM and purchase intentions. This study is not the first one to present these arguments because the arguments also receive support from contemporary researchers including Badenes-Rocha, Ruiz-Mafé, and Bigné [47]; Bialkova and Te Paske [58]; and Chu and Chen [64].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…So, the findings of the present study confirmed that customer CSR engagement on social media positively relates to E-WOM and purchase intentions. This study is not the first one to present these arguments because the arguments also receive support from contemporary researchers including Badenes-Rocha, Ruiz-Mafé, and Bigné [47]; Bialkova and Te Paske [58]; and Chu and Chen [64].…”
Section: Discussionmentioning
confidence: 90%
“…The rise of social media is a game changer in this perspective because it provides a platform to the organizations through which they not only communicate their CSR strategies with different stakeholders like customers but also highlight the importance of their CSR initiative for community and environment [47]. Further, customer-related CSR initiatives of an organization on social media are also important due to their interactive feature because customers and company interactively communicate with each other.…”
Section: Literature Review and Theoritical Supportmentioning
confidence: 99%
“…This investigation is especially relevant, taken that increased message credibility could lift customers trust and thus engagement (Badenes-Rocha et al, 2019). Consumers trust was further associated with brand authenticity (Hernandez-Fernandez and Lewis, 2019), which enhanced brand credibility and value perception (Del Barrio-Garcia and Prados-Peña, 2019).…”
Section: Credibilitymentioning
confidence: 95%
“…Unfortunately, the idea of CSR has been around for the last two decades in Pakistan, but it is still in the early stages, and the majority of the customers do not have a good level of understanding about the importance of CSR knowledge. The rise of social media is a game-changer from this perspective because it provides an interactive platform for the organizations, which they not only communicate their CSR strategies through with different stakeholders, such as customers, but it also highlights the importance of their CSR initiatives for the community and the environment [ 42 ]. Furthermore, CSR initiatives of an organization on social media are also important because of the interactive feature of social media.…”
Section: Theory and Hypothesesmentioning
confidence: 99%